„Idea rosyjska” w ideologii Putina - de Lazari, Andrzej (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
It was Fedor Dostoevskii who introduced the category of “Russian idea” into ideological discussion. Today the category is again in its heyday in Russian nationalism and appears even in Vladimir Putin’s statements. Some believe that Putin puts Aleksandr Solzhenitsyn’s concept into practice. In my text I attempt to question this stance.